Association and diagnostic value of serum SPINK4 in colorectal cancer - Xie,Mingzhi; Li,Kezhi; Li,Jilin; Lu,Dongcheng; Hu,Bangli (PeerJ, 2019)
The role of serum serine peptidase inhibitor, Kazal type 4 (SPINK4), in colorectal cancer (CRC) is largely unknown. This study aimed to explore the association and diagnostic value of serum SPINK4 in CRC. A total of 70 preoperative CRC patients, 30 postoperative CRC patients, 30 gastric cancer patients, and 30 healthy controls were enrolled. Using enzyme-linked immunosorbent assays, we found that the serum SPINK4 level was significantly increased in preoperative CRC compared with postoperative CRC patients, gastric cancer patients, and healthy controls (p < 0.05). The serum SPINK4 level was remarkably elevated in colon cancer compared with rectal cancer and was enhanced in the M1 stage compared with the M0 stage (p < 0.05). The area under the receiver operating characteristic curve of serum SPINK4 level in the diagnosis of CRC was 0.9186, with a sensitivity and specificity of 0.886 and 0.900, respectively, and a cut-off value of 2.065. There was no significant difference between high and low expression of serum SPINK4 regarding the overall survival time and disease-free survival (p > 0.05). This study demonstrated that the serum SPINK4 level increased in CRC and was associated with the location and distant metastasis of CRC. It had a high diagnostic value in CRC but was not associated with the survival of CRC patients.
Keywords: Colorectal cancer; SPINK4; Diagnosis; Prognosis; Serum